2020
DOI: 10.1186/s13195-020-00654-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential blood biomarkers for early diagnosis of Alzheimer’s disease through RNA sequencing analysis

Abstract: Background: With demographic shifts toward older populations, the number of people with dementia is steadily increasing. Alzheimer's disease (AD) is the most common cause of dementia, and no curative treatment is available. The current best strategy is to delay disease progression and to practice early intervention to reduce the number of patients that ultimately develop AD. Therefore, promising novel biomarkers for early diagnosis are urgently required. Methods: To identify blood-based biomarkers for early di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 57 publications
2
55
0
Order By: Relevance
“…The three SNPs associated with the risk of AD on CR1 , CLU , and PICALM chromosome loci (rs3818361, rs11136000 and rs3851179) were genotyped in 148 NCGG samples, representing 80 patients with AD and 68 cognitively normal (CN) adults. We further performed RNA-sequencing analysis of 32 blood samples, composed of 5 ADs and 27 CNs [ 28 ]. The gene expression data were normalized using the trimmed mean of M values (TMM) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The three SNPs associated with the risk of AD on CR1 , CLU , and PICALM chromosome loci (rs3818361, rs11136000 and rs3851179) were genotyped in 148 NCGG samples, representing 80 patients with AD and 68 cognitively normal (CN) adults. We further performed RNA-sequencing analysis of 32 blood samples, composed of 5 ADs and 27 CNs [ 28 ]. The gene expression data were normalized using the trimmed mean of M values (TMM) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we identified the shared transcriptomic signatures between AD and DM by integrating co-expression, DE, and DC analyses. Numerous studies used the DE method between two statuses (disease and control) to identify genes related with a specific disease [ 7 , 8 , 9 , 12 , 13 , 14 ]. However, the DE-based methods cannot reveal two genes that are simultaneously upregulated or downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis identified the immune and inflammation-, energy-, WNT-, endoplasmic reticulum-, and cancer-related pathways as the underlying mechanisms associated with the AD status [ 12 ]. Moreover, RNA-sequencing data of blood samples collected from AD Japanese subjects stored at the National Center for Geriatrics and Gerontology (NCGG) Biobank also revealed several other pathways (i.e., signal-recognition particle (SRP)-dependent cotranslational protein targeting to membrane, translational initiation, and ribosome) associated with the AD status [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The differential expression of RPL27 and RPS15A was validated in TBI mice (Harper et al, 2020 ). Recent studies have shown that RPL7 and RPL23A are differentially expressed in senile dementia and may be potential biomarkers (Shigemizu et al, 2020 ). RPS4X interacts with exogenous lactate dehydrogenase A (LDHA) in the central nervous system and is critical for the proliferation of vascular endothelial cells (Lin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%